Telmisartan combined with probucol effectively reduces urinary protein in patients with type 2 diabetes: A randomized double‐blind placebo‐controlled multicenter clinical study†: 替米沙坦联合普罗布考可有效降低2型糖尿病肾病患者尿蛋白:一项随机、双盲、安慰剂对照、多中心临床研究. (29th December 2015) - Zhu, Hanyu; Chen, Xiangmei; Cai, Guangyan; Zheng, Ying; Liu, Moyan; Liu, Wenhu; Yao, Hebin; Wang, Yaping; Li, Wenge; Wu, Hua; Lun, Lide; Zhang, Jianrong; et al.
Abstract: Background: Persistent proteinuria is an important factor contributing to the progression of diabetic nephropathy. The present randomized double‐blind placebo‐controlled multicenter clinical study evaluated the efficacy and safety of telmisartan combined with the antioxidant probucol in reducing urinary protein levels in patients with type 2 diabetes (T2D). Methods: Patients with T2D and 24‐h proteinuria 0.5–3 g were enrolled in the study and randomly assigned to one of two groups: a telmisartan or a probucol + telmisartan group. Both groups were given telmisartan 80 mg q.d. for 48 weeks. The probucol + telmisartan group was given probucol 500 mg b.i.d. for the first 24 weeks, with the dosage then reduced to 250 mg b.i.d. for the remaining 24 weeks. The telmisartan group was given probucol placebo. Results: In all, 160 patients were enrolled in the present study. The 24‐h proteinuria levels were significantly reduced in the probucol + telmisartan compared with telmisartan group. For patients with baseline 24‐h proteinuria levels <1.0 g, both treatments resulted in significant reductions in 24‐h proteinuria levels after 48 weeks treatment. However, in patients with baseline 24‐h proteinuria levels ≥1.0 g, 24‐h proteinuria levels after 48 weeks treatment were only reduced in the probucol + telmisartan group. There was no significant difference between the two groups for either adverse cardiovascular or other events. Conclusions: In patients with diabetic nephropathy, probucol combined with telmisartan more effectively reduces urinary protein levels than telmisartan alone.